2020
DOI: 10.3201/eid2612.200084
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Retrospective Review of Psychiatric Consultations in Lassa Fever, Southern Nigeria

Abstract: camels continue to be the source of human infections through separate zoonotic transmission events without sublineage separation between viruses in camels and humans. In conclusion, our study suggests multiple lineage 5 clade B viruses continue to be dominant among camels in eastern Saudi Arabia. Camels imported from Sudan and Somalia also had evidence of MERS-CoV B lineage 5 clade viruses prevalent in the Arabian Peninsula, rather than clade C viruses known to be enzootic in camels in Africa. These data sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“… 12 13 Okogbenin et al in a retrospective analysis of psychiatric consultations in patients with Lassa fever infection concluded that mental health intervention could improve overall outcomes of Lassa fever disease. 25 Also, Okogbenin and Seb-Akahomen had recommended mental health and psychosocial intervention via telemental health services as a useful alternative to face-to-face intervention, a model they reported helped ameliorate the mental health effects of COVID-19 infection in patients at the Irrua Specialist Teaching Hospital’s treatment and isolation centre in Nigeria. 26 Apparently, deliberate efforts are needed to address the mental health and psychosocial effects of COVID-19 in persons with the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 13 Okogbenin et al in a retrospective analysis of psychiatric consultations in patients with Lassa fever infection concluded that mental health intervention could improve overall outcomes of Lassa fever disease. 25 Also, Okogbenin and Seb-Akahomen had recommended mental health and psychosocial intervention via telemental health services as a useful alternative to face-to-face intervention, a model they reported helped ameliorate the mental health effects of COVID-19 infection in patients at the Irrua Specialist Teaching Hospital’s treatment and isolation centre in Nigeria. 26 Apparently, deliberate efforts are needed to address the mental health and psychosocial effects of COVID-19 in persons with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…These manifestations may not only persist beyond the pandemic but may lead to increased illness, prolonged stay in the hospital, poorer health outcomes and avoidable strain on healthcare systems and scarce resources if not recognised and managed promptly 12 13. Okogbenin et al in a retrospective analysis of psychiatric consultations in patients with Lassa fever infection concluded that mental health intervention could improve overall outcomes of Lassa fever disease 25. Also, Okogbenin and Seb-Akahomen had recommended mental health and psychosocial intervention via telemental health services as a useful alternative to face-to-face intervention, a model they reported helped ameliorate the mental health effects of COVID-19 infection in patients at the Irrua Specialist Teaching Hospital’s treatment and isolation centre in Nigeria 26.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Okogbenin et al in a retrospective analysis of psychiatric consultations in patients with Lassa fever infection concluded that mental health intervention could improve overall outcomes of Lassa fever disease. [25] Also, Okogbenin and Seb-Akahomen had recommended mental health and psychosocial intervention via tele mental health services as a useful alternative to face-to-face intervention, a model they reported helped ameliorate the mental health effects of COVID-19 infection in patients at the Irrua Specialist Teaching Hospital’s treatment and isolation centre in Nigeria. [26] It is becoming apparent that deliberate efforts are needed to address the mental health and psychosocial effects of COVID-19 in persons with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The main focus of prevention is "community hygiene," to control the rat population [15][16][17][18].…”
Section: Preventionmentioning
confidence: 99%